Navigating Blind in the Green Rush: Clinical Considerations and Harm Reduction Practices for Cannabis - Meffert, Brienna N. (Curr Drug Res Rev, 2019)
BACKGROUND. The United States has recently experienced extensive changes in state policy regarding the use of cannabis for recreational and medicinal purposes. Despite its rapidly increasing accessibility and social acceptance, there is a striking dearth of research on cannabis as a treatment for medical and psychological conditions. Research on cannabis is difficult to conduct as it is classified as a schedule I drug with high potential for abuse and currently no accepted medical use in treatment. As a result, no standard dosing procedures exist and the lack of conclusive scientific evidence has left clinical providers without evidence-based guidelines about if, when, and how to guide clients on using cannabis safely. OBJECTIVE. To (1) provide critical psychoeducational information about cannabis and cannabis problems to guide client-provider conversations about cannabis use and (2) describe common clinical concerns around cannabis use, highlight special considerations for vulnerable populations, and review harm reduction techniques and practical resources that may help clinicians and their clients navigate safer cannabis use. CONCLUSION. The removal of regulatory barriers would enable researchers to address key public health questions about the potential therapeutic and adverse effects of cannabis use. Additionally, funds for research, clinician education, and public health education initiatives are necessary to reduce risk around cannabis use in the United States.